Representação social do ensinar: a dimensão pedagógica do habitus professoral - Melo, Elda Silva do Nascimento (2009)
Teaching is an activity inherent to the human condition. Historically, from the institutionalization of education, the key role to pursue that activity has been attributed to the teacher, who is required to adapt to the demands of each historical conjuncture. Currently, according to the new paradigmatic requirements, the teacher must possess various skills in order to handle the complex and challenging act of teaching. Assuming the existence of a gap between what the State and the scientific discourse recommend the teacher act upon in the classroom, a decision was made to identify the configuration and structure of social representation in the act of teaching, put forth by elementary school teachers in the public schools of Natal, RN, Brazil. Therefore, the research relied on the theoretical model developed by Domingos Sobrinho (1998, 2000, 2003), which articulates the praxeology of Pierre Bourdieu with the theory of social representations of Serge Moscovici (1978). It was intended to demonstrate how teachers habitus, in its due historical context, directs the construction of social representations in the act of teaching which guides the actions of the teacher, particularly in the classroom context. At the methodological level, the following methods and techniques were used: bibliographic and documentary review in order to identify the scientific discourse on the subject matter and the official parameters of educational regulation and the act of teaching; the Procedure of Multiple Classifications PMC in order to capture the configuration and structure of the representational content in focus, the direct observation of the classroom to identify in actual terms the social representation as "guide to action" as the theory preaches. From the standpoint of the analysis, quantitative data were analysed through Multidimensional Scaling MDS, covering in this study the Multidimensional Scale Analysis MSA and Smallest Space Analysis SSA; and non-parametric statiscal techniques. Additional data of qualitative value had to undergo categorical content analysis. It was then concluded that the teachers investigated guided themselves by social representation, the product of collectively constructed and shared assumptions about the act of teaching, forming a synthesis of different sources of information and knowledge acquirement, involving elements of common sense, religious habitus, pedagogic models considered outdated, the agencies responsible for teacher training and the hegemonic discourse about education today